TRANSFORMASI DIGITAL DALAM PROMOSI REAL ESTATE: ANALISIS IMPLEMENTASI AUGMENTED REALITY PADA KARYA MAHASISWA ARSITEKTUR SEBAGAI REPRESENTASI INOVASI DIGITAL NATIVE - Dedi Suardika, I Made; Prarabda Karma, Made; Ratna Witari, Made; Mariada Rijasa, Made (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2025)
This study analyzes the implementation of Augmented Reality (AR) technology inarchitecture students' works in Real Estate courses as a representation of digital nativereadiness to face digital transformation in the property industry. Using a mixed-methodapproach with sequential explanatory design on three student projects: Skandinavilla (Villa27), Modern Villa Seminyak, and Sundara Town House. Analysis was conducted throughcontent analysis, comparative analysis, and thematic analysis. Results show that all threeprojects demonstrated consistency in using QR codes as AR gateway with varied promotionstrategies. Students showed high digital fluency with excellent to good technical integration,high content quality, and excellent marketing alignment. Digital native architecture studentshave developed significant digital competencies in integrating AR technology, reflectingreadiness to contribute to Indonesia's real estate industry digital transformation.